Respuesta :
This equation is not factor-able, so we can use the quadratic formula.
x=(-11+square root(11^2-4(-12*-3)))/(2*-12)
x=(-11+square root(-23))/(-24)
Since we have the square root of a negative in this equation, there are no real roots for the quadratic.
x=(-11+square root(11^2-4(-12*-3)))/(2*-12)
x=(-11+square root(-23))/(-24)
Since we have the square root of a negative in this equation, there are no real roots for the quadratic.
[tex]-12x^2+11x-3=0 \\\\ discriminant: \ b^2-4ac=11^2-4 \times (-12) \times (-3)=121-144=-23[/tex]
discriminant < 0 , No real roots
discriminant < 0 , No real roots